The exploration and evaluation of groundwater units south and west of Graaf-Reinet, Cape Province, South Africa - Parsons, Roger Paul (Rhodes University, Faculty of Science, Department of Geography, 1987)
The investigation reported in the thesis concerns an area south and west of Graaff-Reinet, in the Cape Province. The research projec t identified the existence of four groundwater units. The aquifers predominantly occur in Beaufort Group sediments and the boundary of each unit is formed by dolerite intrusives or with topographical highs. The objective of the study was to quantitatively assess these units in terms of both quantity and quality for possible future development as a municipal supply for Graaff-Reinet. In order to achieve the objective, fieldwork was carried out involving a hydrocensus, geological mapping, drilling, aquifer testing and hydrochemical sampling. The analysis of these data revealed that the Sundays and Kamdeboo aquifer units are unsuitable for further development. The Moordenaars and Swart units, both of which produce good quality water, have a combined exploitation potential in the order of 30 000 mÂ³ /d.,KMBT_363,Adobe Acrobat 9.53 Paper Capture Plug-in
Keywords: Hydrogeology -- South Africa; Aquifers -- South Africa -- Graaff-Reinet; Groundwater -- South Africa -- Graaff-Reinet